Vector model of Professional Identity Development in Modern Specialists with Different Levels of Psychological Well-Being in the Context of Digitalization in Professional Environments - Мehirban М. Abdullaeva; Мaria А. Titova; Vadim A. Emelin; Еlizaveta М. Pechkovskaya (Lomonosov Moscow State University, 2023)
Background. The study of professional identity in modern specialists is associated with the need to ensure their psychological well-being in an increasingly complicated professional environment because of the inclusion of information and computer means of work. The present research continues the construction of a conceptual model for the professional identity in the context of digitalization. Objective. The present stage of our investigation is aimed at constructing a model of professional identity of the modern specialist that allows to outline trends and directions of its changes in the system of self-evaluation as a professional and to link those evaluations with experiencing psychological well-being. Methods. The respondents are offered the questionnaire for demographic data, the "Trust in technology" questionnaire (Akimova, 2020), the semantic differential for assessing oneself as a professional (Serkin, 2016), C. Ryff's scale of psychological well-being in adaptation by T.D. Shevelenkova and T.P. Fesenko (2005), L.B. Schneider's method for studying professional identity (2001), and free associations to the word "technique" to identify the respondents' ideas about it. Sample. 150 respondents (50 men, 100 women) with an average age of 40 years (from 21 to 63) and an average work experience of 18 years (from 2 to 45 years) who work in different professional digital fields. Results. The present paper describes the structure of ideas about technology, the core of which includes such associations as "a computer", "technology", "progress", convenience", "telephone", "innovation", and "modernity". The zone of changes includes "work", "the future", and "the new" which confirms the digitalization of life and activity of a modern specialist. Those data have been completed by a strong trust in technology and a high degree of its mastering. It identifies three clusters based on the level of psychological well-being which are not associated with the respondents' statuses of professional identity but relate to the self-evaluation as a professional. A two-dimensional space constituted by two factors: the level of qualification and capacity for work has been constructed. In relation to them, the statuses of professional identity are distributed to determine vectors of possible changes. Conclusion. The ideas of specialists about technology represent the main trends in the digitalization of professional tools: expanding the range of devices used and their positive assessment. Professional identity of 47 per cent of the respondents is precocious, characterized by the recognition of their own authority but, at the same time, the lack of their independence. Only each third person in this group shows a high level of well-being. The vector model of professional identity constructed in the factor space of self-evaluation as a professional enables to outline the main directions of change in the identity according to two parameters: professional one (content oriented) and individual-personal one (performance). Practical application of the results. The obtained results broaden the existing ideas about the professional identity of working people with different levels of psychological well-being and allow to outline the directions of their psychological support.